2021
DOI: 10.1111/asj.13566
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated metabolism and behaviors by disrupting gut microbiota in prenatal and neonatal mice

Abstract: The live microbiota ecosystem in the intestine plays a critical role in maintaining the normal physiological and psychological functions in both animals and human beings. However, the chronic effect of microbiota disturbances during prenatal and neonatal developing periods on animal's health remains less studied. In the current study, pregnant ICR mice were fed with an antibiotic diet (7‐g nebacitin [bacitracin‐neomycin sulphate 2:1]/kg standard diet) from day 14 of conception, and their offspring were provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…1a ). Similar to the literature 33 , early-Abx treatment slightly reduced the mouse body weight (Supplementary Fig. 1a ).…”
Section: Resultssupporting
confidence: 88%
“…1a ). Similar to the literature 33 , early-Abx treatment slightly reduced the mouse body weight (Supplementary Fig. 1a ).…”
Section: Resultssupporting
confidence: 88%
“…Most studies adopting similar ABX recipes did not observe any change in locomotion 20 22 , except for one study that showed increased locomotion 18 and another study that showed the opposite trend 19 . Another study adopting a single antibiotic in mice showed a reduction in locomotion, which was similar to our findings 62 , 63 . Both GF and antibiotic methods are powerful ways to eliminate commensal organisms.…”
Section: Discussionsupporting
confidence: 92%
“…Two other studies showed that an acute [ 81 ] or chronic [ 59 ] gavage dosing of a single antibiotic in mice increased corticosterone levels upon acute stress exposure. Intriguingly, developmental treatment of mice with antibiotics reduced corticosterone levels under various conditions [ 47 , 82 , 83 ]. The treatment of rats with antibiotics yielded a reduction in corticosterone, indicating a model-dependent effect [ 84 , 85 ].…”
Section: Introductionmentioning
confidence: 99%